ANALISIS PENGARUH FAKTOR - FAKTOR PEMBANGUN TRUST TERHADAP PARTISIPASI PENGGUNA PADA C2C E - COMMERCE STUDI KASUS : FORUM JUAL BELI KASKUS - Windarsyah Windarsyah; Hendrik Hendrik; Teduh Dirgahayu (Teknoin, 2013)
C2C (consume r-to -consumer) e-commerce is currently growing fast in Indonesia. A C2C ecommerce website provides a marketplace in which buyers and sellers meet and make commercial transactions. Such a transaction requires high trust from both parties, since marketplaces typically have no or less sufficient mechanisms to assure that a transaction is safe. This paper analyses whether several factors that build trust has influence on one's willingness to participate in a transaction in a C2C e-commerce website. Factors that are considered are structural assurance, familiarity, perceived similarity, perceived reputation and perceived risk. Data are collected using a Likert-scaled questionanaire from 109 respondents i.e. The users of FJB (Forum Jual Beli, trading forum) Kaskus. Data are analysed using the SEM (Structural Equation Model) method. The results show that (i) perceived reputation has positive and significant influence on trust; and (ii) trust has positive and significant influence on participation